A Comparative Study of Graft-Take Between Tie-Over Dressing and Dressing with Multiple Quilting in Full Thickness Skin Graft (Bangladesh Journal of Plastic Surgery, 2014)
A skin graft is the simplest way of reconstructing an area of skin loss. The graft must acquire blood supply from the wound bed and taken by the recipient site. The aim of the present study was to compare the outcome of graft-take of full thickness skin graft by tie-over dressing versus multiple quilting and simple dressing in face and neck region. This prospective, interventional, comparative study was conducted in the Department of Plastic Surgery, Dhaka Medical College Hospital from January 2009 to December 2010 (2 years). A total number of 60 cases from 56 patients of any age of both sexes requiring full thickness skin graft and fulfilling the pre-set inclusion and exclusion criteria, were selected for the study. Of whom 30 cases were tagged as Group A (Quilting) while the rest 30 as Group B, which was managed with tie-over dressing. Variable outcomes like epidermal loss, partial dermal loss and full thickness loss were observed in both groups. In quilting group excellent result was achieved in 22(73.3%), good 2(6.7%), satisfactory 3(10%) and poor in 3(10%) patient. In tie-over group, it was 19(63.3%), 3(10%), 3(10%) and 5(16.7%) accordingly. So, the good take were 27(90%) in quilting group and 25(83.3%) in tie-over group. Haematoma recorded in 3 (10%) of quilted group and 5 (16.7%) of tie-over group. No infection occurred in any cases of any group. There were no other recorded complications or adverse outcomes directly related to the technique for securing the grafts in either group. The results demonstrate no significant difference in graft-take comparing grafts secured with a tie-over dressing or by quilting. DOI: http://dx.doi.org/10.3329/bdjps.v3i2.18249 Bangladesh Journal of Plastic Surgery July 2012, 3(2): 38-44